Gut microbiota and functional dyspepsia: a two-sample Mendelian randomization study - Xv, Yichuan; Chen, Jiaxu; Lin, Jiang (Frontiers in Microbiology, 2024)
Background: Numerous studies have established that alterations in the gut microbiota (GM) constitute an embedded mechanism in functional dyspepsia (FD). However, the specific GM taxa implicated in the pathological process of FD have remained unclear.Methods: A two-sample Mendelian randomization analysis was initially conducted to examine the causal relationships between GM and FD, utilizing GWAS data from the MiBioGen Consortium (18,340 cases) and FinnGenn (8,875 cases vs. 320,387 controls). The MR study primarily employed the inverse-variance weighted (IVW) method. Sensitivity analyses were performed to test for heterogeneity and pleiotropy.Single-nucleotide polymorphisms of causal GM taxa were mapped to genes, which were subsequently assessed for causal relationships with FD employing the same methodology.Results: IVW results revealed that the genus Clostridium innocuum group (OR: 1.12, 95% CI: 1.02-1.24, P = 0.020) and genus Ruminiclostridium 9 were positively associated with FD risk (OR: 1.27, 95% CI: 1.03-1.57, P = 0.028), while the genus Lachnospiraceae FCS020 group tended to exert a negative effect on FD risk (OR = 0.84, 95% CI: 0.73-0.98, P = 0.023). Among GM-related genes, a notable association was observed between RSRC1 and increased FD risk (OR = 1.13, 95% CI: 1.07-1.20, P < 0.001). In sensitivity analyses, no significant pleiotropy or heterogeneity of the results was found.Conclusions: This study furnished evidence for distinct effects of specific GM taxa on FD risk and hinted at a potential biological mechanism, thereby offering theoretical underpinning for future microbiotherapy of FD.